International Spillovers of Taxiation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1989)
This paper highlights key issues pertinent for the understanding of international effects of domestic tax policies and of international tax harmonization. The analytical framework adopts the saving-investment balance approach to the analysis of international economic interdependence focusing on income, consumption, and international borrowing. A simulation model is developed that is richer in structure than the two period analytical model. The analytical and simulation frameworks are used to analyze the consequences of revenue-neutral conversions between income and consumption (VAT) tax systems, the international effects of budget deficits and public-debt management, and the effects of international tax harmonization. We demonstrate that the effects of such changes in the structure of taxes depend critically on international differences in saving and investment propensities.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet